Analisis Kinerja Jalan Berdasarkan Metode MKJI 1997 Pada Jalan Sinar Peusangan Matangglumpangdua - Iqbal, Deni (Jurnal Vokasi Manajemen Dan Rekayasa Infrastruktur Sipil, 2024)
Road performance analysis based on the 1997 MKJI method as information to help solve the performance problems of the Sinar Peusangan road. Road performance studies based on the 1997 MKJI method are considered necessary to overcome the density of vehicle flow that occurs during rush hour and road sections and several problems found in this road corridor include the development of land use activities that cause movement pulls, disturbances from pedestrians, stopped goods transportation, and parking on the road body which ultimately causes passing vehicles to reduce vehicle speed and has an impact on the emergence of congestion. The purpose of this study is to determine the performance of the Sinar Peusangan road section at this time whether or not it has met road performance standards. Based on the results of the study, it was obtained that the peak morning traffic volume occurred on Monday at 07:00-10:00 which was 121 pcu/hour, the afternoon peak hour occurred on Tuesday at 11:00-15:00 which was 202 pcu/hour and the afternoon peak hour on Tuesday at 15:00-18:00 which was 122 pcu/hour. The side barriers of Jalan Sinar Peusangan are 329.1 SF/hour with a medium class (M) with special conditions, namely industrial areas with shops on the side of the road (300-489). The capacity of Jalan Sinar Peusangan is 1817 smp/hour with a traffic flow on Tuesday of 444 smp/day, the degree of saturation is 0.24, while the lowest day is Monday with a traffic flow of 395, the Degree of Saturation is 0.21.